The Impact of Social Media on Political Participation - MIR AADIL BASHIR (CV. Radja Publika, 2025)
In recent years, social media has emerged as a transformative force in the political landscape, reshaping the ways in which citizens engage with political processes and express their opinions. This paper explores the multifaceted impact of social media on political participation, particularly in democratic societies. By analyzing existing literature, case studies, and empirical data, the study examines how platforms like Facebook, Twitter (X), and Instagram influence civic engagement, voter turnout, protest mobilization, and the formation of political opinions. The paper finds that while social media significantly enhances access to political information and facilitates civic dialogue, it also raises concerns regarding misinformation, polarization, and echo chambers. The conclusion highlights the dual role of social media as both an enabler and a disruptor of political participation.